2008
DOI: 10.1002/ch.349
|View full text |Cite
|
Sign up to set email alerts
|

The use of virtual reality hypnosis with two cases of autism spectrum disorder: a feasibility study

Abstract: The use of a 'virtual reality' hypnotherapeutic procedure was trialled for feasibility as a possible treatment modality for autism (4 sessions over 2 weeks) with 2 boys aged 14 and 15 years old. The aim of the study was to determine if the procedure would be acceptable to autistic patients and thus have some potential as an intervention for reducing anxieties and/or alleviating symptoms associated with autism. Results indicated that the procedure had no effect on autistic symptoms, however, the parents of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Communication and language has also been a target of many behavioral interventions during this review period [39*,4045,46*,47,48*,49,50*,5153,54*,55,56]. The vast majority of communication and language interventions utilized a single-subject design and focused on the development of spoken communication.…”
Section: Communication and Language Interventionsmentioning
confidence: 99%
“…Communication and language has also been a target of many behavioral interventions during this review period [39*,4045,46*,47,48*,49,50*,5153,54*,55,56]. The vast majority of communication and language interventions utilized a single-subject design and focused on the development of spoken communication.…”
Section: Communication and Language Interventionsmentioning
confidence: 99%
“…The additional, very interesting aspect of the therapeutic solution analysed by our team refers to the use of clinical hypnosis in order to broaden the scope of therapeutic methods. In the earlier years, it was found that VR may have the utility as an effective medium for hypnosis [ 12 , 13 ] and it is an effective intervention in lowering the levels of pain and anxiety in patients with burn pain [ 14 ], decreasing the stress level [ 15 ], or treating Post Traumatic Stress Disorder (PTSD) [ 16 ]. The results presented by Thompson et al seem to be extremely interesting; they found on the basis of conducted Randomized Controlled Trial (RCT) that for individuals with low levels of trait absorption, self-rated psychological engagement (vividness of imagery, freedom from distraction, sustained concentration) was significantly higher when hypnosis with VR imagery was used.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality hypnosis (VRH) is a new and promising technology that uses a head mounted display to create a controlled virtual environment adapted to various techniques required in a hypnotherapeutic program [33][34]. Virtual reality hypnosis captures attention at the present moment and eliminates distracting stimuli, so it can be beneficial for those with attention deficits.…”
Section: Virtual/augmented Reality Hypnosismentioning
confidence: 99%
“…Virtual technologies provide sensory stimuli in a controlled virtual environment. Austin et al [33] conducted a feasibility study to uncover the strengths and the weaknesses of virtual reality hypnosis as an intervention tool in two boys 14 and 15 years old with severe autism. The results showed that this technique relaxed and gained patients' attention, but the procedure had no effects on autistic symptoms.…”
Section: Virtual/augmented Reality Hypnosismentioning
confidence: 99%